Microcosms and the role of active microbiota on methane cycle in soils under forest and pasture of Eastern Amazon - Nakamura, Fernanda Mancini (2019)
Amazonian soils are being converted to agricultural lands. Changes in soil coverage and management drive modifications in the chemical and physical soil attributes, which influences the microbiota structure and biological roles. A great portion of the C and N cycling in soil are driven mostly by microbial activity, and the biological cycle of greenhouse gases (GHGs) on Amazonian soils can be influenced by soil use changes and climate changes. The magnitude of those changes in the Amazon Forest can impact considerably the biogeochemical cycles from this tropical area. Advanced molecular studies allied to stable isotope incorporation by soil microbiota can link the identity to function, besides their ecological relation with soil chemical and physical components. This study aimed to evaluate the dynamics of microbiota associated to the methane cycling of Amazonian soils in transitional land-uses. Also, evaluate the factorial effects of these land-uses subjected to climate changes predictions for this biome in a modified soil moisture and temperature. The specific objetive is evaluate these effects throught methane-enriched atmosphere for detection of methanotrophs and methanogens, besides other groups in a trophic network supplied with derived methyl-compounds. Microcosms were set in biological triplicates with intact core soil samples of Oxisols under Pristine Forest and Pasture of Eastern Amazon, in State of Pará, Brazil. In the first chapter, we had three moisture-modulated groups per point in 17%, 35% and 70% v.v. at field capacity, with factorial incubation in two groups of temperature, 25°C or 30°C, and incubation with natural atmosphere. In the second chapter, we had three moisture-modulated groups per point in 17%, 35% and 70% v.v. at field capacity at 30°C, and two groups of incubation, 12CH4 or 13CH4. Samples were all stored in closed headspace for 15 days in the dark. Gases CH4, CO2 and N2O were measured in gas chromatography. Marker genes were absolute quantified in Real-time PCR for methanotrophs (pmoA), methanogens (mcrA), 16S rRNA genes for Bacteria and Archaea. In the first chapter it was demonstrated that Forest and Pasture under wetness and 5°C above actual increased the microbial populations and lead to CH4 emission. In addition, Forest under drought release CH4; and Pasture under drought release N2O. We conclude that specific factorial conditions of land-use, soil type, soil moisture and temperature lead to divergent responses by the microbiota associated to the methane cycle in tropical soil. In the second chapter it was demonstrated that the methane-enrichments, with 12CH4 or 13CH4, were able to stimulate microbial growth among the three tested moistures from the two land-uses. We addressed taxonomy to methane cycle associated functions and relate them to the system conditions, finding specific land and/or moisture related groups. Overall we conclude that under the predictions for climate changes in Amazonian biome, the drought for Western Amazon and wetness for Eastern Amazon can lead to drastic changes on soil microbiota associated with methane and other GHGs, changing the hitherto known inventory for natural emissions from tropical lands.